A photoelectrochemical sensor through quenching of photoinduced electrons based on a G-quadruplex/hemin complex1. Issue 9 (7th May 2015) - Yan, Xiang; Wang, Kewei; Xie, Danping; Xu, Lijun; Han, Qianqian; Qi, Honglan; Pei, Renjun
<x xml:space="preserve">Abstract</x> A novel label-free photoelectrochemical sensor was fabricated for the detection of K+ based on the electron withdrawal effect of hemin. The decreasing photocurrent from photoinduced electron transfer by a G-quadruplex/hemin complex was utilized.